Crop Diversification in Arunachal Pradesh : A Study of Lohit and Lower Dibang Valley Districts - Mossang, Konlom; Gurung, Dil Bahadur (Arthshastra Indian Journal of Economics & Research, 2025)
Purpose : The present study examined the changes in cropping patterns and analyzed the trends and patterns of crop diversification in the Lohit and Lower Dibang Valley districts of Arunachal Pradesh. Methodology : The study is based entirely on secondary data covering the period from 2010–2011 to 2020–2021 and used basic statistical techniques such as percentages, tables, and line graphs, along with the Gibbs-Martin index, to analyze the trends and patterns of crop diversification. Findings : The study found a shift toward diversification in favor of food grain crops over non-food grain crops in both Lohit and Lower Dibang Valley districts. The Gibbs-Martin index revealed an increasing trend in crop diversification in Lohit, whereas it indicated a declining trend in Lower Dibang Valley. However, the index values remained relatively high in both districts, which indicated the cultivation of a wide variety of crops by farmers. Practical Implications : The present study highlighted the need to strengthen crop diversification, particularly toward commercial crops in the sample districts, while addressing the decline in food grain area at the state level. A region-specific strategy, such as improving storage facilities, roads, irrigation, market access, input availability, and technical training, was essential to ensure sustainable crop diversification. Originality : This paper provided insights into the evolving cropping patterns and the crop diversification trends in the selected districts of Arunachal Pradesh.